(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify stressful life events among boarding school students. And stressful life events among students residing in Baghdad Governorate. The significance of the differences in stressful life events among boarding school students and their peers from Baghdad Governorate residents. The significance of the differences in stressful life events among boarding school students and their peers from Baghdad Governorate residents according to the female variable. The significance of the differences in stressful life events among boarding school students and their peers from Baghdad Governorate residents according to the male variable. The significance of the differences in stressful life events among students of internal departments and their peers from residents of Baghdad Governorate according to the scientific specialization variable. The significance of the differences in stressful life events among boarding school students and their peers from Baghdad Governorate according to the humanitarian specialization variable. The current research was limited to students of the internal departments at Al-Mustansiriya University in the Ibn Al-Haytham and Ibn Sina Complex from the morning preliminary studies and of both genders (males - females) and for the academic year (2023/2024). To achieve the research objectives, the researcher adopted the Al-Dhalmi scale (2012) consisting of (43) items, and after verifying the validity and reliability of the scale, he applied the scale to a sample consisting of (320) male and female students. The results showed the following: that the students of internal departments have a low level, and that the students Among the residents of Baghdad Governorate, the score was low. There is a difference between the students of the internal departments and their peers, in favor of the females of the internal departments, and a difference between the females of the internal departments and the females of Baghdad residents, and in favor of the females of the internal departments. There is no difference between males in internal departments and residents of Baghdad, and there is no difference between students in internal departments and residents of Baghdad Governorate in scientific specialization. There is a difference between the students of the internal departments and the residents of Baghdad in the humanitarian specialization and for the benefit of the students of the internal departments. The researcher recommended a set of recommendations and proposals.